2019
DOI: 10.1002/jcp.28577
|View full text |Cite
|
Sign up to set email alerts
|

PE_PGRS62 promotes the survival of Mycobacterium smegmatis within macrophages via disrupting ER stress‐mediated apoptosis

Abstract: Mycobacterium tuberculosis, the leading causative agent of tuberculosis, remains one of the most deadly infectious pathogens. PE_PGRS proteins become a new focus as their species specificity in mycobacteria, especially in pathogenic mycobacteria.Despite intensive research, PE_PGRS proteins are still a mysterious aspect of mycobacterial pathogenesis with unknown mechanism. Herein, we focused on a PE_PGRS member from M. tuberculosis, PE_PGRS62, characterized by a surfaceexposed protein function in disrupting pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…PE_PGRS30 and PE_PGRS47 knockout strains lost the ability to inhibit phagosome fusion ( Iantomasi et al, 2012 ; Saini et al, 2016 ). Similarly, overexpressed PE_PGRS62 significantly inhibits phagosome maturation ( Huang et al, 2012 ; Thi et al, 2013 ; Long et al, 2019 ). During phagocytosis, the transcription level of PPE25 is upregulated, and PPE25 mutant strain loses its ability to replicate within macrophages and prevent phagosome-lysosome fusion ( Jha et al, 2010 ).…”
Section: Role Of Pe/ppe Proteins In Host–pathogen Interactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…PE_PGRS30 and PE_PGRS47 knockout strains lost the ability to inhibit phagosome fusion ( Iantomasi et al, 2012 ; Saini et al, 2016 ). Similarly, overexpressed PE_PGRS62 significantly inhibits phagosome maturation ( Huang et al, 2012 ; Thi et al, 2013 ; Long et al, 2019 ). During phagocytosis, the transcription level of PPE25 is upregulated, and PPE25 mutant strain loses its ability to replicate within macrophages and prevent phagosome-lysosome fusion ( Jha et al, 2010 ).…”
Section: Role Of Pe/ppe Proteins In Host–pathogen Interactionsmentioning
confidence: 97%
“…Recent studies indicate that PPE32 ( Deng et al, 2016 ) and PE_PGRS5 ( Grover et al, 2018 ) are involved in ER stress-mediated cell apoptosis. Conversely, PE_PGRS62 ( Long et al, 2019 ) and PE_PGRS18 ( Yang W. et al, 2017 ) can decrease apoptosis and enhance survival rate. PE31 increased guanylate-binding protein-1 (GBP-1) expression and inhibited caspase-3 activation and macrophage apoptosis through the NF-κB pathway ( Ali et al, 2020 ).…”
Section: Role Of Pe/ppe Proteins In Host–pathogen Interactionsmentioning
confidence: 99%
“…PE_PGRS41 also inhibits the activation of caspase‐3 and caspase‐9, thus apoptosis (Deng et al, 2017). Heterogeneous expression of PE_PGRS62 in M. smegmatis inhibits endoplasmic reticulum stress response (ERS)‐mediated cell apoptosis (Huang et al, 2010; Long et al, 2019).…”
Section: Pe_pgrs Proteins Promote Mycobacterial Survival Through the mentioning
confidence: 99%
“…Mtb PE_PGRS family proteins are the most abundant cell wall anchored proteins that are implicated in bacilli adhesion, invasion, and survival within macrophages and dendritic cells [23]. PE_PGRS62, PE_PGRS41, and PE_PGRS18 contribute actively to revoke macrophage apoptosis [24][25][26].…”
Section: Anti-apoptotic Determinants Of Mycobacteriummentioning
confidence: 99%
“…The ectopic expression of PE_PGRS62 in M. smegmatis enhances its survival within THP-1 macrophages and reduces cell apoptosis. It has been observed that PE_PGRS62 can inhibit the endoplasmic reticulum (ER) stress response ( Table 1) by downregulating C/EBP homologous protein (CHOP) and the 78-kDa glucose-regulated protein (GRP78/Bip), which are essential pro-apoptotic factors in response to stress conditions [25]. Likewise, M. smegmatis-expressing PE_PGRS41 induces much lower THP-1 macrophage apoptosis than the M. smegmatis expressing vector.…”
Section: Anti-apoptotic Determinants Of Mycobacteriummentioning
confidence: 99%